A Laser Scanner–Stage Synchronized System Supporting the Large-Area Precision Polishing of Additive-Manufactured Metallic Surfaces. (December 2021) - Cui, Mengjia; Lu, Libin; Zhang, Zhen; Guan, Yingchun
Abstract: This paper proposes a scanner–stage synchronized approach emphasizing a novel control structure for the laser polishing of Inconel 718 components manufactured by selective laser melting in order to address increasing demands for high surface quality in metal additive manufacturing. The proposed synchronized control system is composed of a motion decomposition module and an error synthesis module. The experimental results show that stitching errors can be avoided thanks to continuous motion during laser processing. Moreover, in comparison with the existing step-scan method, the processing efficiency of the proposed method is improved by 38.22% and the surface quality of the laser-polished area is significantly enhanced due to a more homogeneous distribution of the laser energy during the material phase change. The proposed synchronized system paves the way for high-speed, high-precision, and large-area laser material processing without stitching errors.